140-GHz subwavelength transmission imaging for foreign body inspection in food products. (March 2018) - Ok, Gyeongsik; Park, Kisang; Lim, Min-Cheol; Jang, Hyun-Joo; Choi, Sung-Wook
Abstract: Non-diffractive beam scanning in the millimeter and terahertz wave ranges can provide extended depths of focus and high spatial resolutions for foreign body imaging inspection in food products. Here, an axicon lens was utilized to focus a 140-GHz Bessel–Gauss beam carrying a finite energy and realizing such a beam. An axicon lens array was employed to acquire transmission images using this beam. Even a 1.1 mm-linewidth element could be discriminated at 140 GHz ( λ  = 2.14 mm), where the focused beam spot diameter (0.84 λ ) was almost identical to its theoretical value (0.79 λ ). A 1 mm-linewidth foreign body (in this case, a paper clip) in a food product was successfully identified using the subwavelength imaging system. Highlights: Foreign bodies in food were detected with raster scanning in millimeter wave range. Subwavelength transmission imaging was demonstrated with Bessel-Gauss beams. High resolution and long DOF were concurrently realized with subwavelength optics.